IMPLEMENTASI PRINSIP GOOD CORPORATE GOVERNANCE PADA KEGIATAN PENANAMAN MODAL BERDASARKAN UNDANG-UNDANG NO. 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Ni Putu Ayu Diah Novianti (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Investment activities have increased, by implementing GCG principles it is expected to provide added value to companies, especially investment companies. Where in essence there must be openness to the value of shares to be traded. The purpose of this writing is to find out the arrangements in the Limited Liability Company Law regarding the implementation of GCG Principles. This writing uses a normative research methodology, namely by reviewing based on legal rules, applicable legislation. The principles of GCG, GCG or Good Corporate Governance are good corporate governance with the aim of protecting the rights and interests of shareholders, being able to increase company value, help work efficiency and effectiveness, and improve the quality of the Company. Based on the 5 basic principles of GCG, including transparency, accountability, responsibility, independence and equality. The implementation of the GCG Principles is carried out during the open bidding process, namely by disclosing the value of the shares to be traded, then setting the rights in investment the right of inquiry Article 138 Paragraph (3) UUPT, Derivative rights Article 97 Paragraph (6) UUPT, Right to precedence in Article 43 Paragraphs (1) and (2) of the Company Law, the right to defend their interests in Article 62 paragraph (1) of the Company Law, individual rights as stipulated in Article 61 paragraph (1) of the Company Law.